2022
DOI: 10.3390/cancers14061424
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and Common Features of Numerical and Structural Chromosomal Instability across Different Cancer Types

Abstract: A large proportion of tumours is characterised by numerical or structural chromosomal instability (CIN), defined as an increased rate of gaining or losing whole chromosomes (W-CIN) or of accumulating structural aberrations (S-CIN). Both W-CIN and S-CIN are associated with tumourigenesis, cancer progression, treatment resistance and clinical outcome. Although W-CIN and S-CIN can co-occur, they are initiated by different molecular events. By analysing tumour genomic data from 33 cancer types, we show that the ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Single-cell omics are needed to characterize these reorganized karyotypes. Methods are also required to convert the sequence data into cytogenetic data ( Zhang and Kschischo, 2022 ). Tang et al recently developed a single-cell genome sequencing method based on the third-generation sequencing (TGS) platform, called SMOOTH-seq (single-molecule real-time sequencing of long fragments amplified through transposon insertion).…”
Section: The Methodological Progress Of Single-cell Omics and Single-...mentioning
confidence: 99%
“…Single-cell omics are needed to characterize these reorganized karyotypes. Methods are also required to convert the sequence data into cytogenetic data ( Zhang and Kschischo, 2022 ). Tang et al recently developed a single-cell genome sequencing method based on the third-generation sequencing (TGS) platform, called SMOOTH-seq (single-molecule real-time sequencing of long fragments amplified through transposon insertion).…”
Section: The Methodological Progress Of Single-cell Omics and Single-...mentioning
confidence: 99%
“…Despite their apparently distinct mechanism, it is worth mentioning that both NCIN and SCIN often coexist in tumors ( 7 ). NCIN can induce SCIN and vice versa ( 22 ). In addition, the two types of CIN also have different consequences ( 23 ).…”
Section: Overview Of Chromosomal Instabilitymentioning
confidence: 99%
“…For example, NCIN often leads to DNA damage and p53 activation, while SCIN often leads to chromothripsis etc, which further aggravate GI ( 7 ). In terms of drug therapy, SCIN is more sensitive to chemotherapy and prone to drug resistance to afatinib, lapatinib and austocystin D, while NCIN is more sensitive to radiotherapy and prone to drug resistance to BRAF inhibitors ( 22 ). The differences in various aspects between these two types of CIN suggest that it is necessary to refine CIN.…”
Section: Overview Of Chromosomal Instabilitymentioning
confidence: 99%
“…Oncogene activation, through genetic changes such as mutations or copy number gains (Vogelstein et al, 2004;Albertson et al, 2003) causing genome instability is an early driver of tumorigenesis (Kotsantis et al, 2018). In fact, it was reported that copy number gains of several oncogenes such as MYC or CCNE1 (encoding Cyclin E) are frequently detected in chromosomally unstable cancer cell lines (Berg et al, 2017;Davoli et al, 2013;Habermann et al, 2010;Simone et al, 2002;Zhang and Kschischo, 2022). Overexpression of MYC or CCNE1 were described to cause mitotic spindle assembly defects by deregulation of microtubule organization and chromosome alignment defects resulting in aneuploidy (Keck et al, 2007;Rohrberg et al, 2020).…”
Section: A Possible Link Between Oncogene-induced Rs and Aneuploidy?mentioning
confidence: 99%